Contagion and hygiene in European avant-garde visual art, theatre, and literature
1 online resource.
Keywords: "This interdisciplinary collection of essays brings together scholars in the fields of art history, theatre, visual culture, and literature to explore intersections between the European avant-garde (c. 1880-1945) and themes of health and hygiene, such as illness, contagion, cleanliness, and contamination. Examining the artistic oeuvres of some of the canonical names of modern art - including Edgar Degas, Edvard Munch, Pablo Picasso, George Orwell, Marcel Duchamp, Antonin Artaud - this book investigates instances where the heightened political, social, and cultural currencies embedded within such hygienic issues have been mobilised, and subversively exploited, to fuel the critical strategy at play. This edited volume promotes an interdisciplinary and socio-historically contextualised understanding of the criticality of the avant-garde gesture and cultivates scholarship that moves beyond the limits of traditional academic subjects to produce innovative and thought-provoking connections and interrelations across various fields. The book will be of interest to scholars working in art history, literature, theatre, cultural studies, modern history, medical humanities, and visual culture"--